1966
DOI: 10.1037/h0023868
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to displaced and delayed visual feedback from the hand.

Abstract: S viewed an oscilloscope trace of a short bar which appeared at the position of his nonvisible right hand. The motion of the trace was equivalent to the movements of the hand, which were restricted to a frontal plane. The bar could be optically displaced by 20 diopter prisms, either to the left or right, and its motion could be made to lag behind that of the hand by 1 of 6 delay intervals ranging from 0.0 to 3.0 sec. Results show that the adaptation to displacement found with no delay is completely eliminated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
104
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(105 citation statements)
references
References 8 publications
1
104
0
Order By: Relevance
“…Despite the existence of a large body of psychophysical work, a clear understanding of the kind of information acquired and stored by the nervous system during prism adaptation has only begun to emerge (Cohen 1966;Held et al 1966;Hardt et al 1971;Welch et al 1974;Jakobson and Goodale 1989). Thus, it has been shown that visual feedback is a relevant factor for the onset of the adaptation because introducing a delay between the movement itself and the visual perception of its result reduces the speed at which the accommodation occurs (Kitazawa et al 1995).…”
mentioning
confidence: 99%
“…Despite the existence of a large body of psychophysical work, a clear understanding of the kind of information acquired and stored by the nervous system during prism adaptation has only begun to emerge (Cohen 1966;Held et al 1966;Hardt et al 1971;Welch et al 1974;Jakobson and Goodale 1989). Thus, it has been shown that visual feedback is a relevant factor for the onset of the adaptation because introducing a delay between the movement itself and the visual perception of its result reduces the speed at which the accommodation occurs (Kitazawa et al 1995).…”
mentioning
confidence: 99%
“…However, various lines of evidence indicate that this solution is subject to severe temporal constraints. Modest additional delays in feedback can significantly slow or attenuate motor learning (Held et al 1966;Held and Durlach 1989;Honda et al 2012;Kitazawa et al 1995;Kitazawa and Yin 2002). For example, Kitazawa et al (1995) estimated that, during prism adaptation, a 50-ms delay of the visual feedback results in a 50% reduction in the learning rate.…”
mentioning
confidence: 99%
“…Hence, at the outset, the operator has not only little information about the remote scene, but also limited means of transmitting timely high fidelity video and other data. Yet, research has shown that tele-operation performance is significantly degraded with delays of as small as 0.4 seconds [10]. This causes operators to lose direct intuitive connection between their control actions and effects at the remote site displayed in the video feedback.…”
Section: Introductionmentioning
confidence: 99%